1935
DOI: 10.1002/path.1700410214
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in the organs of rats injected with œstrone alone or simultaneously with æstrone and testicular hormone

Abstract: A DETAILED investigation of the effect of cestrone * administered alone or simultaneously with testicular hormone is important (1) because the testes secrete both these hormones and (2) because pathological changes have been described in some of the organs of male rats after the administration of aestrone. Moore and Price (1932) by injecting aestronc into male rats obtaincd n marked decrease in the size of the testes, seminal vesicles nnd prostate. Simultaneous injection of testicular hormone prevented atroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1936
1936
1979
1979

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…When the pathological changes due to injections of estrogen had been established, Rusch (16) found that adequate doses of androgen caused a reversal of the epithelial changes although the increase of stroma was not reduced. In the rat, male hormone administered with estrone completely prevented the pathological changes in the prostate (32). In the monkey swelling of the sexual skin and metaplasia in the prostate were suppressed by simultaneous injections of male hormone (33,34,36).…”
Section: Spontaneous Prostatic Enlargement In the Dog--this Conditiomentioning
confidence: 95%
See 1 more Smart Citation
“…When the pathological changes due to injections of estrogen had been established, Rusch (16) found that adequate doses of androgen caused a reversal of the epithelial changes although the increase of stroma was not reduced. In the rat, male hormone administered with estrone completely prevented the pathological changes in the prostate (32). In the monkey swelling of the sexual skin and metaplasia in the prostate were suppressed by simultaneous injections of male hormone (33,34,36).…”
Section: Spontaneous Prostatic Enlargement In the Dog--this Conditiomentioning
confidence: 95%
“…Korenchevsky and Dennison (14) reported that the prostate glands of rats similarly treated were much smaller than those of control rats, although they were larger than the glands of castrated rats. They found that changes in the ventral and lateral lobes were slight, while in the posterior lobes significant epithelial metaplasia and connective tissue hypertrophy developed (32). Selye (15) found that estradiol produced a decrease in weight of the prostate glands as compared with uninjected controls.…”
Section: Spontaneous Prostatic Enlargement In the Dog--this Conditiomentioning
confidence: 99%
“…From the Pharmacology Department, University of Edinburgh (Received 17 July 1957) For more than twenty years it has been known that female sex hormones and some of their synthetic substitutes produce adrenal hypertrophy when administered to rats (Korenchevsky & Dennison, 1935;Selye, Couip & Thomsen, 1935; Noble, 1939;and others). This hypertrophy is accompanied by a diminution of the lipid content (Loeser, 1939;Vogt, 1945).…”
Section: By Margarethe Holzbauermentioning
confidence: 99%
“…
It has been known for a long time (Korenchevsky & Dennison, 1935; Selye, Collp & Thomsen, 1935) that oestrogens cause hypertrophy and hyperplasia of the rat adrenal cortex. Selye & Collip (1936) have shown that this effect is absent in the hypophysectomized rat, even when the adrenal cortex is maintained by adrenocorticotrophic hormone (ACTH).
…”
mentioning
confidence: 99%